A compact jet at the infrared heart of the prototypical low-luminosity AGN in NGC 1052. Issue 4 (14th March 2019) - Fernández-Ontiveros, J A; López-Gonzaga, N; Prieto, M A; Acosta-Pulido, J A; Lopez-Rodriguez, E; Asmus, D; Tristram, K R W
Abstract: The feeble radiative efficiency characteristic of Low-Luminosity Active Galactic Nuclei (LLAGNs) is ascribed to a sub-Eddington accretion rate, typically at log ( L bol / L edd ) ≲ −3. At the finest angular resolutions that are attainable nowadays using mid-infrared (mid-IR) interferometry, the prototypical LLAGN in NGC 1052 remains unresolved down to \!5 mas (0.5 pc ). This is in line with non-thermal emission from a compact jet, a scenario further supported by a number of evidences: the broken power-law shape of the continuum distribution in the radio-to-UV range; the 4 per cent degree of polarization measured in the nuclear mid-IR continuum, together with the mild optical extinction (A_V 1 mag ); and the 'harder when brighter' behaviour of the X-ray spectrum, indicative of self-Compton synchrotron radiation. A remarkable feature is the steepness of the IR-to-UV core continuum, characterized by a power-law index of ∼2.6, as compared to the canonical value of 0.7. Alternatively, to explain the interferometric data by thermal emission would require an exceptionally compact dust distribution when compared to those observed in nearby AGN, with A_V 2.8 mag to account for the IR polarization. This is in contrast with several observational evidences against a high extinction along the line of sight, including the detection of the nucleus in the UV range and the well-defined shape of the power-law continuum. The case of NGC 1052 shows that compact jets can dominate the nuclear emission in LLAGN across the whole electromagnetic spectrum, a scenario that might be common among this class of active nuclei.